Μελέτη της επίδρασης της ξηρασίας στη βιοσύνθεση των φλαβονοειδών στο σταφύλι από το περκασμό μέχρι την πλήρη ωρίμανσης - Παναγή, Ελένη (Department of Agricultural Sciences, Biotechnology and Food Sciences, Cyprus University of Technology, 2013)
Grapevine is an important crop because of its high fruit content in nutrients as well as other compounds such as flavonoids, with various protective and antioxidant role. Flavonoids constitute a class of compounds produced by the secondary metabolism of higher plants and they have been shown to impart antioxidant properties in both plants and human organism. Several studies have described that the biosynthesis of flavonoids is influenced by various environmental factors such as light, temperature, presence of plant hormones and the availability of water in the soil. Plant growth under conditions which deviate from the optimal growth conditions seems to induce the biosynthesis of flavonoids. The current study aims to investigate the effects of drought in the regulation of the expression of seven biosynthetic genes (CHS2, CHI1, FLS1, DFR, ANR, LAR1and UFGT) and a transcription factor (MybA1) implicated in the flavonoid biosynthetic pathway in grape (variety "Syrah"), in seven developmental stages (from the start of veraison to full maturity). The project was conducted in two consecutive seasons (2011-2012) in order to examine the variability of the data due to possible microclimate (‘terroir’) differences. To study the regulation of the expression of genes involved in the biosynthesis of flavonoids, molecular analysis was performed using RNA isolation (CTAB protocol method), complementary DNA (cDNA) synthesis following real-time RT-PCR (qRT-PCR) with UBQ as a house-keeping gene. The analysis of the results showed that drought stress affects the expression levels of the tested genes, with a general induction of the expression, and therefore the biosynthesis of flavonoids in full maturity. Additionally, there were no differences in the regulation of gene expression studies between the two consecutive periods, although individual differences in the levels of gene expression (factor of induction/suppression) were observed. Moreover, physiological and analytical measurements were carried out for determining the impact of drought in weight and content of total phenolic compounds and anthocyanins in ripe berries. These analyses revealed that the weight is negatively correlated with drought, while the content of total phenolics and anthocyanins was positively correlated. Concluding, the application of water deficit induces the biosynthesis of flavonoids, decreases the size of berries and increases the content of phenolic compounds in the developmental stage of full maturity.
Keywords: Grapevine; Flavonoids